Level of Services (LOS) for public bus and passenger’s aspiration in Kerian District, Malaysia - Bachok, Syahriah; Mohamed Osman, Mariana; Ponrahono, Zakiah (e-International Publishing House, Ltd., UK., 2018)
Public transportation facilitates the mobility of activities and goods from all sustainable development key dimensions. Over the past decades, more trips of public transportation move people towards a more sustainable future, by reducing congestion on the roads and increasing the efficiency of the road system. The research aims at analysing the passenger’s aspiration and perspective of sustainable public transport measure and evaluating Malaysian rural bus services, using the case study of Kerian District in the state of Perak. On-board intercept passenger survey and adoption of Geographical Information System (GIS) / Global Positioning System (GPS) were used to collect the primary data. The research suggested that whilst the services levels are less than those aspired by the passengers, there are many improvement areas to be prioritised in the near future.